Implementasi Pembelajaran Literasi Numerasi pada Program Kampus Mengajar untuk Meningkatkan Kemampuan Belajar Siswa SD Negeri Tanrara - Nur Ayu; Muhammad Syukur (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Students' learning abilities related to implementing literacy and numeracy as knowledge and abilities that are closely related to understanding numbers, symbols and analysis of quantitative data such as graphs, tables, charts, generation which are very important to have at this time. By having good literacy and numeracy skills, students are capable of applying their mathematical knowledge in real life. The teaching campus program is part of the Merdeka Campus program. The aim is to provide opportunities for students and self-development through actions outside the lecture period. students will be placed in elementary schools throughout Indonesia and will assist in the learning process at school. Literacy and numeracy are important concepts needed in efforts to develop Indonesia's human resources (SDA). In the current situation, literacy and numeracy do not only cover the ability to read, write and count. However, literacy and numeracy are defined as life skills that cover many aspects of one's life. One of the indicators for measuring developed countries is studying the level of literacy and also the lives of its inhabitants.